Driver see, driver crash: Associations between televised stock car races' audience size and the incidence of speed-related motor vehicle collisions in the United States. Issue 1 (2nd January 2019) - Roden-Foreman, Jacob W.; Foreman, Michael L.; Funk, Geoffrey A.; Powers, Mark B.
Abstract: Several studies have examined road rage, but few studies have examined other psychosocial factors that may contribute to the number of motor vehicle collisions (MVCs). One study found increases in MVCs in West Virginia following televised NASCAR races but did not account for audience size. This study examined associations between NASCAR's television viewership ratings and the incidence of speed-related MVCs in the USA using generalized estimating equations that controlled for seasonal effects, intoxication, road surface conditions, and lighting conditions. A 1% increase in the number of US households watching NASCAR races per month was associated with a 6.3% (95% confidence interval [CI], 3.0% to 9.7%; P  < 0.001) increase in the incidence of speed-related MVCs—approximately 4911 (95% CI, 2353 to 7470) speed-related MVCs per month or one speed-related MVC per 595 (95% CI, 382 to 1354) viewers. As expected, similar results were not found for the total number of MVCs. These data suggest that televised NASCAR races may be associated with substantial increases in the incidence of speed-related MVCs. Making drivers aware of psychological factors that may increase risky driving behaviors could prove beneficial because self-monitoring can result in safer driving.